Perawatan luka jahitan perineum pada ibu nifas Di PMB Emy Lestari Purworejo - Rahmawati, Isabella (Infomasi dan Promosi Kesehatan, 2023)
Introduction : The postpartum period is an important thing to attention in order to reduce maternal and infant mortality in Indonesia. The direct causes of maternal death in Indonesia are currently, infection (10%), and other causes. others (15%). The cause of puerperal infection from injury to the birth canal which is development of germs because the mother's immune after giving birth is still low, poor care and poor hygiene (Prawirohardjo, 2008). The study was conducted for 6 weeks from 28 October to 9 December 2019 at PMB Emy Lestari Purworejo, 10 postpartum mothers were found, of these 7 postpartum mothers has perineal wound. So, the author interested to research on postpartum mothers at PMB Emy Lestari Purworejo. Purpose: Knowing the effectiveness of perineal wound care in perineal wound healing in postpartum mothers at PMB Emy Lestari Purworejo. Methods: The type of research method used is descriptive analytic method. This research instrument used the results of examinations, observations or observations of the author, interviews with clients and supporting data listed in the maternal and child health book owned by the client. Results : The results of perineal wound care in postpartum mothers, 2 patients were slightly dry wounds on the 4th day, while 3 patients received slightly dry wounds on the 4th day, while the wound was slightly dry on day 6 in 2 patients.Conclusions: Caring for perineal wounds by washing with soap and applying betadine is effective to accelerate perineal wound healing and increase the comfort of postpartum women